Apaddharmaparva: Articulating the Dilemma on Ethics and Politics within the Epic, the Mahabharata - Sahgal, Smita (Advances in Social Sciences Research Journal, 2021)
The Mahabharata is an epic with encyclopaedic complexity. It weaves many mundane issues of political and social relevance with those of theology and philosophy. Without doubt the Mahabharata is a troubled story, a story of war and violence. Troubled times beckon distinct solutions, which appear at odds with socially recognized norms. The text understands these solutions in terms of apaddharma, the law of Exigency. We need to locate the concept and theory of apaddharma within the magnum Opus and attempt to comprehend its many layered meaning along with investigating if it were a digression from dharma. The vital issue is to postulate how it came to imply a law in the times of emergency. We mull over a number of issues that push one to use the tool of apaddharma. For instance, how do people negotiate crisis, especially the one that threatens their survival? Can a king justifiably stabilise his rule by becoming violent and what are the limits to political behaviour in the world of realpolitik? How does political conduct be adjusted within the frames of morality that demands steadfast conduct of ethical behaviour? Can the laws of apaddharma come to the rescue of the populace and the king? The dialectics becomes evident as we go deeper into studying the issue though our queries also start getting answered